Hybridisation of mixed transition metal oxide with graphene as advanced electrode material for symmetric supercapacitor application - Low, Wei Hau (2021)
Nowadays, imminent deficiency of fossil fuels and rising environmental concerns have triggered the immense research enthusiasm for the development of green and renewable energy sources. Lately, supercapacitors are emerging as one of the competent energy storage devices owing to their excellent capacitive properties, long term cycling stability as well as remarkable power density. In this sense, the promising family of mixed transition metal oxides (MTMO) possesses felicitous as active electrode materials for supercapacitor due to their multiple oxidation states and ions, leading to superior specific capacitance. Moreover, many researchers are dedicated in hybridising the MTMO with graphene nanosheets as advanced electrode materials due to the peculiar properties of graphene, which ameliorate the electrical conductivity and enlarge the specific surface area of the nanocomposite for Faradaic redox reaction. The current thesis emphasis on the latest evolution of MTMO and the integration of MTMO with graphene nanosheets as active electrode materials, with a comprehensive study of their synthetic approaches. In addition, the energy storage mechanism of distinct types of supercapacitor and the critical factors affecting the electrochemical activities of transition metal oxide-based materials are also delineated.